Pain-related white matter tract abnormalities in mild traumatic brain injury patients with persistent headache. Issue 1 (November 2018) - Leung, Albert; Yang, Eric; Lim, Michael; Metzger-Smith, Valerie; Theilmann, Rebecca; Song, David; Lin, Lisa; Tsai, Alice; Lee, Roland
Background: The occurrence of debilitating chronic persistent (24/7) headache after mild traumatic brain injury represents a central neuropathic pain state. Previous studies suggest that this chronic headache state can be attributed to altered supraspinal modulatory functional connectivity in both resting and evoked pain states. Abnormalities in the myelin sheaths along the supraspinal superior longitudinal fasciculus and anterior thalamic radiation are frequently associated with alteration in pain modulation related to functional connectivity deficit with the prefrontal cortex. This study assessed the correlated axonal injury-related white matter tract abnormality underlying these previously observed prefrontal functional connectivity deficits by comparing the fractional anisotropy, axial diffusivity, and radial diffusivity of brain white matter in patients with mild traumatic brain injury-related headache to healthy controls. Result: Diffusion tensor imaging data from patients ( N = 12, average age ± SD = 35.0 ± 8.0 years old, 10 male) with mild traumatic brain injury-headache were compared with images acquired from healthy controls. The mild traumatic brain injury cohort demonstrated two areas of significant ( P < 0.01, F value >16, cluster size >50 voxels) white matter tract abnormalities closely related to pain affective and modulatory functions in (1) the left superior longitudinal fasciculus which connects the prefrontal cortices with the parietal cortices and (2) the right anterior thalamic radiation connecting the prefrontal cortices with the anterior cingulate cortex. In addition, a significant ( P < 0.01) decrease in axial diffusivity and increase in radial diffusivity at the superior longitudinal fasciculus cluster were noted in the mild traumatic brain injury cohort. Conclusion: The identified white matter tract abnormalities may represent a state of Wallerian degeneration which correlates with the functional connectivity deficit in pain modulation and can contribute to the development of the chronic persistent headache in the patients with mild traumatic brain injury.